THE EFFECT OF THE USE OF GAMIFICATION E-LEARNING ON EMPLOYEE ENGAGEMENT, JOB PLEASURE, AND JOB SATISFACTION IN THE BANKING SECTOR - Girsang, Laverin Imelda; Purba, Heddry; Hutabarat, Francis (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The impact of gamification e-learningon banking employees' engagement, enjoyment,and job satisfaction is the focus of this study. Many businesses are turning to e-learningto improve access and flexibility of training due to the changing digital work environment triggered by the COVID-19 pandemic. This research focuses on how gamification e-learningaffects employee engagement, enjoyment at work, and job satisfaction—byconducting a quantitative study by distributing questionnaires to 114 Standard Chartered Bank employees, selected using probability sampling method through random sampling technique. The positive relationship between e-learning gamificationand the three variables was processed on the SEM-PLS version 3.2.9 application. As a result of this study, gamification e-learningcan significantly increase employee engagement, enjoyment at work,and job satisfaction and has a positive influence. Therefore, this study is expected to inform organizations about the importance of the gamification approach in employee training.